Perspectives on South Asia - Pai Panandiker, V. A., 1935-; Behera, Navnita Chadha; Centre for Policy Research (New Delhi, India) (Delhi : Konark Publishers, 2000)
Selected papers presented at various meetings during 1991-1997.
Includes bibliographical references and index.
Keywords: South Asia -- Politics and government -- Congresses